Aid for trade in Asia and the Pacific promoting economic diversification and empowerment. (Metro Manila, Philippines Asian Development Bank, 2019)
It highlights the roles of services and digital connectivity in facilitating diversification and inclusive economic transformation. The report examines recent trends in aid for trade in Asia and the Pacific and how it can do more to boost inclusive growth.
Keywords: Gender equality; Industry and state; Electronic books